2005
DOI: 10.1103/physrevlett.95.166104
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Ice Monolayer on Atomically Smooth AmorphousSiO2at Room Temperature Observed with a High-Finesse Optical Resonator

Abstract: The structure of an H(2)O monolayer bound to atomically smooth hydroxylated amorphous silica is probed under ambient conditions by near-infrared evanescent-wave cavity ring-down absorption spectroscopy. Employing a miniature monolithic optical resonator, we find sharp (approximately 10 cm(-1)) and polarized (>10:1) vibration-combination bands for surface OH and adsorbed H(2)O, which reveal ordered species in distinct local environments. Indicating first-monolayer uniqueness, the absorption bands for adsorbed H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 37 publications
6
31
0
Order By: Relevance
“…Crystalline silica has a dense ordered network of geminal hydrogen-bonded silanol groups leading to ordered water layers (Notman & Walsh, 2009) (see Fig. 9), while amorphous silica has isolated geminal and hydrogen-bonded silanol groups resulting in only locally ordered regions of water molecules and hydroxyl groups (Aarts et al 2005).…”
Section: Silicon Oxide Surfacesmentioning
confidence: 99%
“…Crystalline silica has a dense ordered network of geminal hydrogen-bonded silanol groups leading to ordered water layers (Notman & Walsh, 2009) (see Fig. 9), while amorphous silica has isolated geminal and hydrogen-bonded silanol groups resulting in only locally ordered regions of water molecules and hydroxyl groups (Aarts et al 2005).…”
Section: Silicon Oxide Surfacesmentioning
confidence: 99%
“…11 Based on optical experiments an ice-like monolayer on amorphous SiO 2 has been proposed at room temperature and 10% relative humidity (RH). 14 Information on the structure of water films thicker than a monolayer is much scarcer. Sumfrequency vibrational spectroscopy experiments have shown a mixture of ice-like and water-like structures on the surface of quartz (0001) immersed in water.…”
Section: Introductionmentioning
confidence: 99%
“…9 On a fully hydroxylated (100) surface these groups are sufficiently close to each other that H-bonded networks can be formed. In the (111) surface the hydroxyl groups are more separated so that no H-bonds can form between them.The structure of water in contact with different SiO 2 surfaces has been studied both theoretically [10][11][12][13] and experimentally [14][15][16][17][18] . These studies have predicted an ordered hexagonal water layer on the hydroxylated surface of quartz (0001) 13 and a hexagonal ice-like structure on a fully hydroxylated β-cristobalite (100) surface.…”
mentioning
confidence: 99%
“…Furthermore, in addition to these crystalline β-crystoballite (1,0,0)-like domains, a weak peak assigned to a tilted surface hydroxyl species indicated the presence of fewer crystalline (1,1,1)-like domains. Upon exposing the relatively dry, quasi-crystalline surface to a high-humidity surrounding, an ordered monolayer of water formed on the surface (84). This study convincingly demonstrated that EW-CRDS has sufficient sensitivity for detecting monolayers, but the results regarding the observed extended network of geminal and isolated hydroxyl groups are less definite.…”
Section: Evanescent-wave Cavity Ring-down Spectroscopy Using Folded Rmentioning
confidence: 65%
“…An advantage of the folded cavity is the straightforward alignment of the system, which allows good measurements even if the sample is isolated from the excitation source and the detection system (e.g., in an ultrahigh vacuum or in a low-humidity chamber). Using mirror coatings centered at 1205 nm, the 2νOH + δOH vibration-combination bands of surface hydroxyls as well as of surface-bound water were probed (84). The observed polarized 2νOH + δOH doublet, assigned to the geminal surface hydroxyls [Si-(OH) 2 groups], indicated the presence of an extended H-bonded network of the germinal hydroxyls.…”
Section: Evanescent-wave Cavity Ring-down Spectroscopy Using Folded Rmentioning
confidence: 99%